Charles Bonnet syndrome: characteristics of its visual hallucinations and differential diagnosis - Thiago Cardoso Vale; Luciene Chaves Fernandes; Paulo Caramelli (Arquivos de Neuro-Psiquiatria)
Objective: To present an eight-case serie of patients with Charles Bonnet syndrome (CBS). Method: All patients were initially evaluated by an ophthalmologist and then submitted to a neurologic evaluation with exclusion of alternative psychiatric and neurologic diagnoses. Results: Five patients were male (62.5%) and the mean age was 52.3+16.0 years. Two patients suffered from severe myopia and glaucoma, three had retinitis pigmentosa, one had anterior ischemic optic neuropathy, one had age-related macular degeneration and one had toxoplasmic retinochoroiditis. Mean visual acuity in the right eye was 1,12 logMAR and in the left eye 0.57 logMAR. A mean delay of 41.7 months occurred until diagnosis. All hallucinations were complexes and mostly ocurred on a weekly-basis (62.5%) and lasted for seconds (87.5%). Conclusions: Physicians who care for low vision patients should be aware of CBS and appropriately diagnose its hallucinations after exclusion of psychiatric and neurologic diseases.